Public Discourse and Socially Responsible Market Behavior - Björn Bartling; Vanessa Valero; Roberto A. Weber; Yao Lan (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We investigate the causal impact of public discourse on socially responsible market behavior. We conduct laboratory market experiments with products that differ in their production costs and social impact, and provide market actors and impacted third parties with the opportunity to discuss appropriate market behavior. Across two studies that vary characteristics of the discourse, the external impact and the participants, we find that public discourse substantially increases market social responsibility. Our findings suggest that discussions and campaigns focusing on appropriate market behavior can be powerful tools for shaping responsible norms governing market conduct and addressing inefficiencies due to market failures.
Keywords: C92; D62; D83; M14; 330; public discourse; market failure; externalities; social responsibility; social norms; experiment; communication